ACHIEVEMENT DIFFERENCES OF BASIC MEANDERING OVER MOTOR ABILITIES OF SKIERS - Rašid Hadžić; Duško Bjelica; Dobrislav Vujović; Stevo Popović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
This research analyzes the techniques involved in basic winding in relation to motor abilities of subjects. The aim of this study was to determine the difference in the technique of primary windings in relation to motor ablities of subjects. Methods: In a sample of 30 students, average age 22 years, male, measuring by 6 measures of motor abilities and one situational-motor test was carried out. The data were analyzed by SPSS 20.0 version. Results and discussion: Alpine skiing technique was assessed through primary windings, the technical element of skiing which is present in the basic form of skiing. Based on these results, we can conclude that, the differences are established and boundaries are clearly defined in the level of adoption of the basic winding techniques between subsamples in relation to motor ablities.